BIOMARKERS AS PALAEOENVIRONMENT AND THERMAL MATURITY INDICATORS OF THE SANDAKAN FORMATION (LATE MIOCENE) EAST SABAH, MALAYSIA - Abubaker, Tarek; Hasiah Abdullah, Wan; Abd. Rahman, Abdul Hadi (Malaysian Journal of Science, 2004)
This paper discusses biomarker distributions and their application as thermal maturity and palaeoenvironmental indicators for the Late Miocene Sandakan Formation. Parameters such as CPI (carbon preference index) and transformation of $C_3_1$ and/or $C_3_2$ 22S/ (22S+22R) hopane ratios, suggest that the samples analysed are thermally immature for oil generation. Very low ratios of $C_3_1$ and/or $C_3_2$ 22S/ (22S+22R) hopanes and very high CPI values are typical of low maturity. Vitrinite reflectance (%$R_0$) supports the low thermal maturity and an absence offeatures indicative of hydrocarbon generation. The dominance of n-$C_3_1$ over n-$C_1_7_$ alkanes, $C_2_9$ over $C_3_0$ hopane and oleanane over $C_3_0$ hopane suggest a high input of terrestrially-derived organic matter. The wide spread in parameters such as pristane/n-$C_1_7$ phytane/n-$C_1_8$, and Pristane/ Phytane ratios may, however, reflect variation in depositional conditions and/or source input within the Sandakan Formation. These samples appear to have been deposited in varying depositional conditions of oxic to sub-oxic to reducing conditions of deposition; of peat-swamp environments to alternating brackish swamps to more open-water conditions. A low relative abundance of tricyclic terpanes suggests only slight marine influence in the depositional setting, with perhaps slightly saline conditions based on minor occurrence of $C_2_4$ tetracyclics and $C_2_3$ tricyclics.